On the multi-scale nature of ski-snow friction: Field testing, characterisation and modelling of cross-country ski performance - Kalliorinne, K. (Luleå University of Technology, 2024)
Most endurance sports aim to get from point A to point B as quickly as possible. Throughout the course, athletes need to overcome the resistive forces that are present in their specifc sport. Cross-country skiing is no exception to this, and there are mainly three resistive forces acting on a skier: the aerodynamic drag force, the friction force, and the gravitational force in the inclined parts of a track. The present work focuses on the resistive force of friction between the ski and the snow. At the highest level of ski sports, a signifcant efort is made to reduce the ski-snow friction, and a slight reduction in friction can signifcantly impact the race outcome. Several aspects are considered when skis are chosen and prepared to minimise friction: ski-camber profle, ski-base material, ski-base texture, and ski-base preparation. Depending on the prevailing snow and weather conditions, the dominating friction mechanisms may vary, so the choices of skis and preparations must be carefully considered and tested accordingly.